Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
B=4*13/9*3-4/3*40/9
B=4/3*13/9-4/3*40/9
B=4/3*(13/9-40/9)
B=4/3*(-27)/9
B=4*(-3)/9
B=-4
A=6/7 + 1/7.(2/7+5/7)
A=6/7 + 1/7.7/7=6/7+1/7.1
A=6/7+1/7=7/7=1
Ta có: \(B=\dfrac{11}{13}\cdot\dfrac{40}{13}+\dfrac{37}{5}:\dfrac{7}{33}-\left(\dfrac{11}{13}+\dfrac{33}{7}:\dfrac{5}{2}\right)\)
\(=\dfrac{440}{169}+\dfrac{37}{5}\cdot\dfrac{33}{7}-\dfrac{11}{13}-\dfrac{33}{7}\cdot\dfrac{2}{5}\)
\(=\dfrac{297}{169}+\dfrac{33}{7}\cdot\left(\dfrac{37}{5}-\dfrac{2}{5}\right)\)
\(=\dfrac{297}{169}+\dfrac{33}{7}\cdot7\)
\(=\dfrac{297}{169}+33=\dfrac{5874}{169}\)
A) 7/38 x 9/11 +7/38 x 4/11 -7/38 x 2/11
=7/38.(9/11+4/11-2/11)
=7/38
B) 5/31 x 21/25 + 5/31 x -7/10 - 5/31 x 9/20
=5/31.(21/25-7/10-9/20)
=5/31.(-31/100)
=-1/20
\(\frac{5^{11}.7^{12}+5^{11}.7^{11}}{5^{12}.7^{12}+9.5^{11}.7^{11}}\)
=\(\frac{5^{11}.7^{11}\left(7+1\right)}{5^{11}.7^{11}\left(5.7+9\right)}\)
= \(\frac{8}{35+9}\)
= \(\frac{8}{44}\)
= \(\frac{2}{11}\)
-370/77
`5/7 . 40/11 - 5/11 . 114/7`
`=5/11 . 40/7 - 5/11 . 114/7`
`=5/11 . (40/7 - 114/7)`
`=5/11 . (-74)/7`
`=(-370)/77`